Evaluation of repeat testing of a non‐sequencing based NIPT test on a Finnish general‐risk population. (10th June 2021) - Karlsson, Filip; Ahola, Tarja; Dahlberg, Jenny; Prensky, Lawrence; Moilanen, Helena; Spalding, Heli
Abstract: Introduction: To evaluate the effect of repeating test failures using an automated, non‐sequencing based non‐invasive prenatal testing test on a general‐risk population in Finland. Material and Methods: A total of 545 samples from women who represent the average‐risk population in Oulu, Finland were analyzed with Vanadis ® non‐invasive prenatal testing. Repeat testing of test failures was performed using a second sample. Results before and after repeat testing were compared with the reference outcome, as determined by clinical examination of neonates. Results: There were eight test failures after first‐pass analysis, representing 1.5% of samples (95% CI 0.6%‐2.9%). Seven out of eight failures could be resolved by analysis of a second sample, thereby reducing the test failure rate from 1.5% to 0.2% (95% CI 0.0%‐1.0%). Conclusions: Repeating test failures with a second plasma sample could significantly reduce the effective failure rate, thereby providing a way to effectively minimize test failures and further improving clinical utility and test performance.